A review of the quill mites of the genus Gunabopicobia Skoracki and Hromada (Acariformes: Prostigmata: Syringophilidae) associated with birds of the order Columbiformes. Issue 7 (3rd October 2018) - Kaszewska, Katarzyna; Skoracki, Maciej; Hromada, Martin
ABSTRACT: Gunabopicobia Skoracki and Hromada, 2013, the only genus of the subfamily Picobiinae Johnston and Kethley, 1973, associated exclusively with birds of the order Columbiformes is reviewed. Five new species are described: G. lathami sp. nov . ex Leucosarcia melanoleuca (Latham) from Australia and ex Caloenas nicobarica (Linnaeus) from Papua New Guinea and Indonesia; G. leptotila sp. nov . ex Leptotila verreauxi Bonaparte from Argentina; G. claravis sp. nov . ex Claravis pretiosa (Ferrari-Pérez) from Colombia; G. geotrygoni sp. nov . ex Geotrygon linearis (Prévost) from Venezuela, ex G. chrysie Bonaparte from Martinique, ex G. frenata (Tschudi) from Colombia, and ex G. montana (Linnaeus) from Paraguay, and G. metriopelia sp. nov . ex Metriopelia melanoptera (Molina) from Argentina. Based on the shape of the propodonotal shield and the coalescence of the setal bases 1a, we established two species groups in the genus Gunabopicobia: zumpti and metriopelia . Additionally, we constructed a key to all species of the genus and discussed the host–parasite relationships between Gunabopicobia species and columbiform birds.